A meta-analytic review of trials that tested whether eating disorder prevention programs prevent eating disorder onset. (July 2021) - Stice, Eric; Onipede, Z. Ayotola; Marti, C. Nathan
Abstract: This report provides a review of randomized controlled trials that tested whether an eating disorder prevention program significantly reduced future onset of eating disorders, which is important because eating disorders are common and result in marked functional impairment. We identified 15 trials involving 5080 participants (mean ages ranging from 14.5 to 22.3) that reported 19 tests of whether selective eating disorder prevention programs significantly reduced future onset of eating disorders relative to some type of minimal control condition or a credible alternative intervention. Healthy lifestyle modification prevention programs, dissonance-based prevention programs, and a self-esteem/self-efficacy prevention program significantly reduced future onset of eating disorders, though the later was only evaluated in one trial. Psychoeducational, cognitive behavioral, behavioral weight gain, interpersonal, and family-therapy-based prevention programs did not significantly reduce future onset of eating disorders. The average prevention effect size was statistically significant ( OR  = 1.64, 95% CI = [1.09, 2.46], t  = 2.54, p  = .020) and there was heterogeneity in effect sizes ( Q [18] = 35.96, p  = .007). Prevention effects were significantly larger for trials that recruited participants with elevations on a single risk factor versus with elevations in multiple risk factors and for healthy lifestyle modification prevention programs versus cognitive behavioral prevention programs, though the remaining examined factors did not moderate intervention effect sizes (e.g., risk of bias). The fact that lifestyle modification and dissonance-based prevention programs significantly reduced future onset of eating disorders in multiple trials, producing a 54% to 77% reduction in future eating disorder onset implies that broadly implementing these prevention programs could reduce the population prevalence of eating disorders. Highlights: Meta-analytic review of prevention programs aimed to reduce eating disorder onset. Identified 15 trials that reported 19 tests of prevention effects. The average prevention effect was statistically significant: OR  = 1.78; 95% CI =1.26, 2.49. Intervention type and single risk factor samples moderated effects. Dissonance-based and lifestyle modification interventions produced largest effects.